PEMANFAATAN AFFAL KULIT PERKAMEN SEBAGAI BAHAN BAKU CINDERAMATA DAN MENGURANGI DAMPAK PENCEMARAN LINGKUNGAN - Entin Darmawati; Sutopo Sutopo; Nuraini Indrati (Politeknik ATK Yogyakarta, 2014)
This study aims to harness the potential of parchment leather affal for raw materials of souvenir coloured with natural dyes. Materials used are parchment affal from sheep/goat, cow and buffalo skin for making puppet. This research used experiment method, consisting of three (3) stages: 1. Identification and inventory of parchment affal potential resulted from leather puppet - making; 2. Process of making souvenirs as accessories for women using natural coloring, with variations : Affal types of parchment ( sheep, cow , buffalo ); accessories design ( earrings; necklace ; brooch ); coloring substance; 3. the color absorption and the potential added value of the affal parchment leather souvenirs. Independent variables (X1 = Affal parchment; X2 = accessories design; X3= natural dyes substances). Dependent Variables (Y1 = color absorption; Y2 = value - added value). Collected data were analyzed using ANOVA (Analysis Of Variance). Presentation of the data presented is in tables, graphs and images. Results of research show that potential of parchment affal from skin of sheep / goat of every crafter = 288.0 kg, cows 324.0 kg and buffalo 306.0 kg / year and 500.0 grams. Optimum product per affal producing earrings = 166 pieces ( sheep / goats ) ; Brooch = 278 pieces (cow) ; Necklace = 48 pieces (buffalo). Natural color absorption is affected by parchment skin histology. It can be concluded that parchment affal has feasibility to be used as raw material for women's accessories.